2011
DOI: 10.1038/eye.2011.168
|View full text |Cite|
|
Sign up to set email alerts
|

Combined 23-gauge microincisonal vitrectomy surgery and phacoemulsification with AcrySof toric intraocular lens implantation: a comparative study

Abstract: Aim To compare AcrySof toric intraocular lens (IOL) and non-toric IOL in patients who had combined 23-gauge microincisional vitrectomy surgery (MIVS) and phacoemulsification for vitreoretinal diseases and cataract with pre-existing corneal astigmatism. Methods This is a prospective comparative study comprised of 30 patients (30 eyes) who had combined 23-gauge MIVS and phacoemulsification for vitreoretinal diseases and cataract with pre-existing regular corneal astigmatism greater than 1 diopters (D). In all, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Holland et al 3 investigated favourable rotational stability of AcrySof toric IOL at 1 year postoperatively and the mean axis rotation was 3.8°. Previously, the authors reported that toric IOL showed favourable results for correcting pre-existing cornea astigmatism and good rotational stability, even in vitrectomised eyes for 6 months 9. However, the follow-up period was not sufficient to evaluate the long-term effect and rotational stability of the toric IOL in vitrectomised eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Holland et al 3 investigated favourable rotational stability of AcrySof toric IOL at 1 year postoperatively and the mean axis rotation was 3.8°. Previously, the authors reported that toric IOL showed favourable results for correcting pre-existing cornea astigmatism and good rotational stability, even in vitrectomised eyes for 6 months 9. However, the follow-up period was not sufficient to evaluate the long-term effect and rotational stability of the toric IOL in vitrectomised eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore it has been proved that the vitrectomized status of eyes does not provoke mispositioning of toric IOL [2]. The similar incidence of rotation to the non-vitrectomized eyes may be derived from the special haptic design and adhesive properties of the AcrySof toric IOL [1, 2, 9]. Our keratoconus patient had cataract, which was induced by a previous vitrectomy.…”
Section: Resultsmentioning
confidence: 77%
“…All of these treatments have limitations including the degree of treatable astigmatism and long-term instability [1]. In the present paper, we report the successful management of two cases with cataract and high astigmatism after posterior segment surgeries, due to scleral buckling or keratoconus.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations